2021
DOI: 10.1093/rap/rkab063
|View full text |Cite
|
Sign up to set email alerts
|

‘All disease begins in the gut’—the role of the intestinal microbiome in ankylosing spondylitis

Abstract: Ankylosing spondylitis is a chronic debilitating arthritis with a predilection for the axial skeleton. It has a strong genetic predisposition, however, the precise pathogenetic mechanisms involved in its development have not yet been fully elucidated. This has implications both for early diagnosis and also effective management. Recently, alterations in the intestinal microbiome have been implicated in disease pathogenesis. In this review we summarise studies assessing the intestinal microbiome in ankylosing sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 101 publications
0
5
0
2
Order By: Relevance
“…Prevotella is associated with dysbiosis and the pathogenesis of arthritis. Studies in patients with AS have shown that Prevotella could be increased or decreased in the gut microbiota; however, its pro-inflammatory potential is widely recognized [ 40 , 41 ]. Moreover, in HLA-B27-positive transgenic rats, Prevotella dysregulates the key pathogenic cytokines, including IL-17, IL-23, and TNF-α [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prevotella is associated with dysbiosis and the pathogenesis of arthritis. Studies in patients with AS have shown that Prevotella could be increased or decreased in the gut microbiota; however, its pro-inflammatory potential is widely recognized [ 40 , 41 ]. Moreover, in HLA-B27-positive transgenic rats, Prevotella dysregulates the key pathogenic cytokines, including IL-17, IL-23, and TNF-α [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In general, loss of the overall diversity, loss of commensal, beneficial organisms or excessive growth of potentially harmful ones, pathobionts, aspects not mutually exclusive, are criteria for diagnosing dysbiosis, a key term in the human microbiome field especially used to mediate the association of microbiome patterns to disease states that need to imply a fine-grained analysis (33,34). Several studies focusing on the intestinal microbiome and how it relates to AS disease revealed alterations in the gut microbiome in patients with AS, but, to date, no distinct AS microbial signature has been identified (35). In spite of the tendency of greater pooled diversity of the HC group than of the AS group which further needs more refined consideration as some of the low abundant or not uniform across the cohort taxa may be a potential source of beneficial or pathogenic organisms, we have limited evidence of a significant difference between the gut microbiomes as a whole in AS patients and healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, establishing causation as opposed to association remains problematic [36]. Thirdly, there is the challenge of establishing whether there exists a characteristic microbiome that is specific to AS patients (Figure 3) [40]. Many of these microbes were thought to be gut commensals, but new studies have shown them to be increased specifically with disease and thus are regarded as pathobiont [36].…”
Section: Infections and Microbiomementioning
confidence: 99%